Prevalence and characteristics of naturally occurring sofosbuvir resistance‐associated variants in patients with hepatitis C virus genotype 1b infection. Issue 13 (8th April 2016) - Ito, Jun; Suda, Goki; Yamamoto, Yoshiya; Nagasaka, Atsushi; Furuya, Ken; Kumagai, Kenichi; Kikuchi, Hideaki; Miyagishima, Takuto; Kobayashi, Tomoe; Kimura, Megumi; Yamasaki, Kazushi; Umemura, Machiko; et al.
Abstract : Aim : Sofosbuvir (SOF), a nucleotide analog pro‐drug, targets hepatitis C virus (HCV) NS5B polymerase and shows potential for treating HCV infection, given its high efficacy and good barrier to resistance. However, in addition to the rare resistant‐associated variant (RAV) of non‐structural protein NS5B S282T, several new potential RAVs of SOF have been reported, especially related to HCV genotype 1b. However, the prevalence and characteristics of these RAVs have not been clarified. Methods : We analyzed the prevalence of variants in the NS3/NS5A/NS5B regions in 96 patients treated with simeprevir (SMV) combination therapy, and the prevalence of RAVs in patients showing treatment failure was determined by direct‐ or deep‐sequencing methods. Associations between these potential RAVs and clinical factors were also analyzed. Results : Prevalence of NS5B RAV C316N was high (46.9%, 45/96), whereas that of NS5B L159F was relatively low (1.04%, 1/96); however, deep sequencing showed that 30.0% of patients with C316N also had NS5B RAV L159F. Additionally, there was no significant relationship between the existence of potential NS5B and NS5A or NS3 RAVs. However, the presence of NS5B C316N was significantly associated with an HCV core amino acid 91 substitution. No significant difference was detected between each RAV and sustained virological response in simeprevir combination therapy. Conclusion : We provide clear evidence of the high prevalence of two potential naturally occurring NS5B RAVs (C316N and L159F) in Japan. It may be important to pay particular attention to these new potential RAVs, especially when using SOF‐based therapy in patients with RAVs due to previous direct‐acting antiviral therapy failure.